Spatial Analysis of Organic Material, CaCO3 and C-Oragnic in Coastal Area, Aceh Besar Regency - Adnan, Amri; Irham*, Muhammad; Rusdi, Muhammad (Graduate School of Universitas Syiah Kuala, 2022)
Most of the coastal zones of Aceh Besar are areas of accumulation of organic compounds such as C-Organic and CaCO3. Therefore, studying the distribution of organic carbon and carbonates in sediments in coastal areas is necessary. This study aims to analyze the distribution of C-Organic and Calcium Carbonate (CaCO3) coupled with pH and Salinity tests spatially on the surface at a depth of 40 - 60 cm in the coastal area of Aceh Besar District. The C-Organic content was analyzed using the Walkley and Black method, while Calcium Carbonate (CaCO3) was analyzed using the Titrimetric method. Soil pH and salinity tests were carried out in situ using a pH meter, and soil salinity tests were tested using a salinometer. The study results show that the distribution of C-Organic and Carbonate content differs in each location in Aceh Besar Coastal area. The distribution of organic carbon and carbonates in the northern part of Aceh Besar, in the Ujong Batee Puteh area, has an average value of 0.86% and 10.28%. While the distribution of C-Organic in the Lamreh area is, on average, 0.44% and carbonate (CaCO3) is 8.03%. On the other hand, in the western part of Aceh Besar, the distribution C-Organic in the Ujong Pancu area is, on average, 2.83%, and carbonate (CaCO3) is 8.05%. The distribution of C-Organic in the Lhok Seudu area has an average value of 1.07% and carbonate (CaCO3) of 9.65%. The results also reveal the fact that there are 3 (three) factors that influence the distribution of C-Organic and CaCO3. These factors are the topographic location that allows the material to be eroded due to runoff, vegetation that enriches organic matter composition, and the depositional environment. The results of the pH distribution test in soil showed that the pH in the coastal area of Aceh Besar is relatively alkaline, and the salinity distribution is relatively low, indicating the absence of seawater intrusion and salt deposits. Further studies need to be carried out for other depth variations to obtain more comprehensive results of other distributions.